The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/iej.12749
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two different concentrations of sodium hypochlorite on postoperative pain following single‐visit root canal treatment: a triple‐blind randomized clinical trial

Abstract: Farzaneh S, Parirokh M, Nakhaee N, Abbott PV. Aim To compare the effects of two different concentrations of NaOCl solution on postoperative pain following single-visit root canal treatment in mandibular molars with irreversible pulpitis. Methodology A total of 122 patients who had mandibular molars with irreversible pulpitis were treated. The patients were randomly divided into two groups according to the concentration of NaOCl used during root canal instrumentation -either 2.5% or 5.25%. RaCe rotary instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 37 publications
2
66
1
Order By: Relevance
“…), 0.5–5.25% NaOCl solutions have been described for use in clinical practice (Baumgartner & Cuenin , Farzaneh et al . ), demonstrating significantly lower postoperative pain than other solutions (Farzaneh et al . ).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…), 0.5–5.25% NaOCl solutions have been described for use in clinical practice (Baumgartner & Cuenin , Farzaneh et al . ), demonstrating significantly lower postoperative pain than other solutions (Farzaneh et al . ).…”
Section: Discussionmentioning
confidence: 82%
“…), demonstrating significantly lower postoperative pain than other solutions (Farzaneh et al . ). It is important to highlight that cultured cells are considerably more sensitive to toxicity induced by chemical agents than periapical tissues (Bajrami et al .…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In a study by Farzeneh et al . 2018, using two different concentrations of sodium hypochlorite as irrigants for single visit root canal treatment in mandibular molar teeth with irreversible pulpitis and no history of spontaneous pain, it was shown that the post‐operative pain occurrence was highest during the first 48 h post‐operatively with both concentrations of sodium hypochlorite . However, it was also reported that increased concentration of sodium hypochlorite had significantly less post‐operative pain occurrence .…”
Section: Discussionmentioning
confidence: 99%